2020
DOI: 10.1111/jgs.16654
|View full text |Cite
|
Sign up to set email alerts
|

Implications of 2020 Skilled Home Healthcare Payment Reform for Persons with Dementia

Abstract: BACKGROUND/OBJECTIVES: The Medicare home health benefit provides episodic skilled home-based clinical care to the growing population of community-dwelling persons with dementia. As of January 1, 2020, home health payment changed: episodes shortened from 60 to 30 days, and episodes initiated in the community are now reimbursed at lower rates than episodes following institutional stays. We aim to assess the potential impact of these policy changes on this population. DESIGN/SETTING: Cross-sectional study using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 25 publications
4
28
0
Order By: Relevance
“…These actions have previously led to reduced access for older adults with greater disability and social vulnerability 18,21,46,47 . Against this backdrop, the January 2020 implementation of the revised home health payment system (PDGM) has prompted concerns that the provisions contained therein, including failure to adjust for cognitive impairment, may threaten home health access for older adults with cognitive impairment 16,17 . Results of the present study amplify these concerns by suggesting that home health agencies incur greater care delivery costs for those with cognitive impairment.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…These actions have previously led to reduced access for older adults with greater disability and social vulnerability 18,21,46,47 . Against this backdrop, the January 2020 implementation of the revised home health payment system (PDGM) has prompted concerns that the provisions contained therein, including failure to adjust for cognitive impairment, may threaten home health access for older adults with cognitive impairment 16,17 . Results of the present study amplify these concerns by suggesting that home health agencies incur greater care delivery costs for those with cognitive impairment.…”
Section: Discussionmentioning
confidence: 71%
“…This echoes research demonstrating an association between cognitive impairment and greater care needs in other care settings. [3][4][5][6]8 While there is limited information specific to home health, prior work indicates that patients with cognitive impairment receive a greater number of visits 17 over a longer period of time, 16 and that receiving more visits lowers the risk of unplanned readmission and institutionalization for these patients. 45 Given this link between care intensity and outcomes, it is concerning that CMS reported a decline in the average number of home health visits provided following the recent payment system revision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our findings confirm the recognized need for supportive home-based services for community-dwelling older adults with cognitive impairment. 10,34 Compared to those without cognitive impairment, cognitively impaired Medicare beneficiaries access HHC at higher rates 35 and using different referral pathways. 22 During HHC they require greater family caregiver support 36 and a greater number of visits (particularly skilled nursing visits).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has shown that albeit having a modest impact on improving outcome measures, HHVBP has not led to any improvement in experience of care in HHC (Teshale et al, 2020). Rather, the value-based payment reform may penalize more CHHAs with fewer clinical and administrative resources, thus worsening the socioeconomic and racial/ethnic disparities in HHC (Ankuda et al, 2020). Multiple quality initiatives have been implemented in HHC since 2012, such as the HHVBP and the more recent PDGM that may have affected the experience of home health care among Medicare beneficiaries and socioeconomic and racial/ethnic disparities (Alliance for Home Health Quality and Innovation, 2021).…”
Section: Discussionmentioning
confidence: 99%